Analisis Psikologi Tokoh pada Novel Debu dalam Angin Karya Pratiwi Juliani (dengan Menggunakan Pendekatan Psikologi) Sastra dan Pemanfaatannya Sebagai Bahan Ajar di SMA - Tanti Winiyanti; Dewi Suprihatin; Suntoko Suntoko (EduInovasi: Journal of Basic Educational Studies, 2025)
Literature is a reflection of human life expressed through language as a medium of emotion and thought. One of the essential aspects of literary studies is character psychology, which helps readers understand the inner state, conflict, and psychological development of a character. This research aims to analyze the psychological aspects of the main character in the novel Debu dalam Angin by Pratiwi Juliani using a literary psychology approach, and to explore its potential as teaching material in high school. The study employs a descriptive qualitative method with library research and text analysis techniques. The findings reveal that the main character undergoes complex psychological dynamics, including internal conflict, past trauma, and a struggle for self-identity. These elements are relevant for use as literary teaching material in high school, especially in fostering empathy, character comprehension, and the internalization of life values.